Learn more about

Refine search


Results (1-50 of at least 1000)

Next   To download results, determine the number of results.
Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
196.a.21952.1 196.a \(y^2 + (x^2 + x)y = x^6 + 3x^5 + 6x^4 + 7x^3 + 6x^2 + 3x + 1\) $E_1$ $0$
363.a.11979.1 363.a \(y^2 + (x^2 + 1)y = x^5 + 2x^3 + 4x^2 + 2x\) $G_{3,3}$ $0$
363.a.43923.1 363.a \(y^2 + x^2y = 11x^5 - 13x^4 - 7x^3 + 10x^2 + x - 2\) $G_{3,3}$ $0$
450.a.36450.1 450.a \(y^2 + (x^3 + 1)y = x^5 - 4x^4 - 9x^3 + 28x^2 - 6x - 16\) $G_{3,3}$ $0$
464.a.29696.1 464.a \(y^2 + (x + 1)y = 8x^5 + 3x^4 - 4x^3 - 2x^2\) $\mathrm{USp}(4)$ $0$
464.a.29696.2 464.a \(y^2 + xy = 4x^5 + 33x^4 + 72x^3 + 16x^2 + x\) $\mathrm{USp}(4)$ $0$
472.a.60416.1 472.a \(y^2 + (x + 1)y = 8x^5 + 5x^4 + 4x^3 + 2x^2\) $\mathrm{USp}(4)$ $0$
504.a.27216.1 504.a \(y^2 + (x^3 + x)y = 3x^4 + 15x^2 + 21\) $G_{3,3}$ $0$
588.a.18816.1 588.a \(y^2 + (x^3 + 1)y = x^5 + x^4 + 5x^2 + 12x + 8\) $G_{3,3}$ $0$
600.a.18000.1 600.a \(y^2 + xy = 10x^5 - 18x^4 + 8x^3 + x^2 - x\) $G_{3,3}$ $0$
600.a.96000.1 600.a \(y^2 + (x + 1)y = 4x^5 + 5x^4 + 3x^3 + 2x^2\) $G_{3,3}$ $0$
600.b.30000.1 600.b \(y^2 + (x^3 + x)y = x^4 + x^2 - 3\) $G_{3,3}$ $0$
630.a.34020.1 630.a \(y^2 + (x^2 + x)y = 3x^5 + 10x^4 - 23x^2 - 6x + 15\) $G_{3,3}$ $0$
640.a.81920.1 640.a \(y^2 + x^3y = 3x^4 + 13x^2 + 20\) $N(G_{1,3})$ $0$
640.a.81920.2 640.a \(y^2 + x^3y = -3x^4 + 13x^2 - 20\) $N(G_{1,3})$ $0$
644.b.14812.1 644.b \(y^2 + (x^3 + 1)y = x^5 - x^4 - 4x^3 + 5x^2 - x - 1\) $\mathrm{USp}(4)$ $0$
676.b.17576.1 676.b \(y^2 + (x^2 + x)y = -x^6 + 3x^5 - 6x^4 + 6x^3 - 6x^2 + 3x - 1\) $E_1$ $0$
704.a.45056.1 704.a \(y^2 + y = 4x^5 + 4x^4 - x^3 - 2x^2\) $\mathrm{USp}(4)$ $0$
708.a.19116.1 708.a \(y^2 + (x^3 + 1)y = -x^5 + 4x^2 + 4x - 1\) $\mathrm{USp}(4)$ $0$
731.a.12427.1 731.a \(y^2 + (x^3 + x^2)y = x^5 + 2x^4 - x - 3\) $\mathrm{USp}(4)$ $0$
741.a.28899.1 741.a \(y^2 + (x + 1)y = -3x^5 - x^4 + 2x^2 + x\) $\mathrm{USp}(4)$ $0$
762.a.82296.1 762.a \(y^2 + (x^2 + x)y = x^5 - 8x^4 + 14x^3 + 2x^2 - x\) $\mathrm{USp}(4)$ $0$
784.a.43904.1 784.a \(y^2 + (x^3 + x)y = 4x^4 + 27x^2 + 56\) $G_{3,3}$ $0$
784.b.12544.1 784.b \(y^2 + (x^3 + x)y = -1\) $G_{3,3}$ $0$
784.b.25088.1 784.b \(y^2 + (x^2 + 1)y = -x^6 - 3x^5 + 7x^4 + 2x^3 - 49x^2 + 41x - 9\) $G_{3,3}$ $0$
784.b.76832.1 784.b \(y^2 + (x + 1)y = -x^6 + 4x^5 - 4x^4 - 2x^3 + 10x - 9\) $G_{3,3}$ $0$
816.a.13872.1 816.a \(y^2 + (x^3 + x^2)y = -2x^4 + 6x^2 - 8x + 3\) $\mathrm{USp}(4)$ $0$
816.a.39168.1 816.a \(y^2 + (x^2 + 1)y = 3x^5 - 4x^3 - x^2 + x\) $\mathrm{USp}(4)$ $0$
816.b.52224.1 816.b \(y^2 + (x^3 + x)y = -x^6 - 12x^4 - 27x^2 - 17\) $G_{3,3}$ $0$
826.a.11564.1 826.a \(y^2 + (x^2 + x)y = x^5 + x^4 + 3x^3 - 4x^2 - 4x + 3\) $\mathrm{USp}(4)$ $0$
882.a.63504.1 882.a \(y^2 + (x^2 + x)y = x^5 + x^4 + x^3 + 3x^2 + 3x + 1\) $G_{3,3}$ $0$
925.a.23125.1 925.a \(y^2 + xy = 5x^5 + x^4 - 19x^3 + 18x^2 - 5x\) $\mathrm{USp}(4)$ $0$
975.a.63375.1 975.a \(y^2 + (x^3 + 1)y = -x^5 + x^3 + 2x^2 + x - 1\) $\mathrm{USp}(4)$ $0$
1008.a.27216.1 1008.a \(y^2 + (x^3 + x)y = -4x^4 + 15x^2 - 21\) $G_{3,3}$ $0$
1083.a.20577.1 1083.a \(y^2 + x^3y = x^5 - 5x^4 + 11x^3 - 13x^2 + 9x - 3\) $G_{3,3}$ $1$
1083.b.87723.1 1083.b \(y^2 + y = -x^6 - 3x^5 - 8x^4 - 11x^3 - 14x^2 - 9x - 6\) $G_{3,3}$ $0$
1104.a.17664.1 1104.a \(y^2 = x^5 - 2x^4 + 4x^3 - 4x^2 + 3x - 1\) $\mathrm{USp}(4)$ $0$
1147.a.35557.1 1147.a \(y^2 + xy = x^5 + 8x^4 + 18x^3 + 8x^2 + x\) $\mathrm{USp}(4)$ $0$
1147.a.35557.2 1147.a \(y^2 + xy = x^5 + 6x^4 - 32x^2 + x\) $\mathrm{USp}(4)$ $0$
1148.a.47068.1 1148.a \(y^2 + (x^2 + x + 1)y = x^5 + 2x^4 - 5x^3 + x\) $\mathrm{USp}(4)$ $0$
1170.a.10530.1 1170.a \(y^2 + (x^2 + x)y = 15x^6 + 28x^5 + 62x^4 + 59x^3 + 62x^2 + 28x + 15\) $G_{3,3}$ $0$
1176.b.16464.1 1176.b \(y^2 + (x + 1)y = -2x^5 + x^2\) $G_{3,3}$ $0$
1180.a.18880.1 1180.a \(y^2 + (x^3 + 1)y = -2x^4 + 4x^2 + 2x\) $\mathrm{USp}(4)$ $0$
1192.a.19072.1 1192.a \(y^2 + (x^3 + x)y = x^3 - 2x^2 - x + 1\) $\mathrm{USp}(4)$ $0$
1197.a.10773.1 1197.a \(y^2 + (x^3 + x^2)y = -x^3 - x^2 - x + 2\) $\mathrm{USp}(4)$ $0$
1200.a.30000.1 1200.a \(y^2 + (x^3 + x)y = -2x^4 + x^2 + 3\) $G_{3,3}$ $0$
1216.a.19456.1 1216.a \(y^2 + x^2y = 4x^5 + 3x^4 - 11x^3 - 6x^2 + 6x - 1\) $\mathrm{USp}(4)$ $0$
1258.a.21386.1 1258.a \(y^2 + xy = x^5 + 4x^4 - 5x^3 - 4x^2 + 5x - 1\) $\mathrm{USp}(4)$ $0$
1280.a.12800.1 1280.a \(y^2 + y = 2x^5 + x^4 - x^3 - x^2\) $\mathrm{USp}(4)$ $0$
1296.a.20736.1 1296.a \(y^2 = x^5 - x^4 - 3x^3 + 4x^2 - x\) $E_3$ $0$
Next   To download results, determine the number of results.